Trans-archive. Magnus Hirschfeld et l’atlas visuel des sexualités de l’entre-deux-guerres - Damien Delille (Genre & Histoire)
The history of the LGBTIQ+ archives created by the German sexologist Magnus Hirschfeld during the inter-war period provides a significant example of a visual research project concerned with modern sexuality. The study of the Scientific and Visual Atlas of Sexuality (1926-1930) allows us to consider the bodies and appearances of marginalized subjectivities, through the analysis of the processes of visualization of medical abnormality, and the visibility of homo and trans sociability. The Institute of Sexology in Berlin, created in 1919, which served as a location for the collection and archival preservation of this queer archeology of non-normative identities, was also inspired by a monistic conception of science and the visual, which Hirschfeld shared with art historian Aby Warburg. Art thus plays a central role in the construction of trans-archives, conceived as an expression of subjectivities, in the process of sexual emancipation, and as a place of performative knowledge of gender identities.